Nepali Hindu Women’s Thorny Path to Liberation - Dhungana, Raj Kumar (Journal of Education and Research, 2014)
This article explains how Nepali Hindu women’s oppressive position was created in the past and how they are still struggling for their full liberation – mukti. It also reflects that Hindu women’s long journey towards freedom and equality has been moving through a thorny path. Deriving mainly from literatures, this paper discusses how Nepali Hindu women’s identity ‘Aimai’ was constructed and how, through their continuous struggle, they are getting better condition as dignified ‘Mahila’ yet far from their reach to the position of fully liberated women –mukta Mahila. DOI: http://dx.doi.org/10.3126/jer.v4i1.10013 Journal of Education and Research, March 2014, Vol. 4, No. 1, pp. 34-52